The Correlation Between The Role of Leadership with Business Success of Cattle Farmers Grouo (Case On Group Farmers SPR Kahuripan, Tegalwaru District, Purwakarta Regency) - Lilis Nurlina; Marina Sulistyati; Ivana Yaspisa Lie (Jurnal Ilmu Ternak, 2019)
The research about the correlation between the role of leadership and business success of cattle farmers group was at members of cattle farmers group at Tegalsari village and Warung Jeruk village on SPR’s programme, District Tegalwaru, Purwakarta Regency. The aims of this research was to : (a)  know the role of leadership the cattle farmers group at group of livestock Mekarjaya and Tegalsaluyu, (b) know the level bussines success of cattle farming at group of livestock Mekarjaya and Tegalsaluyu, and (c) to know the correlation  between the role of leadership and business success of cattle farmers group on SPR’s programme at Mekarjaya and Tegalsaluyu’s groups. The method of research was survey with the technic sampling was proportional random sampling, in order to obtain thirty  respondents. The data was analyzed by using rank Sperman correlation. The result of research showed that: 1)  The role of leadership on farmer livestock   Mekarjaya and Tegalsaluyu groups belong to good category. 2) the business success of cattle farming at group of livestock Mekarjaya and Tegalsaluyu belong to fair category. 3)There was positive strong correlation between the role of leadership with business success of cattle farmer group (rs= 0.87).